Interpretação forense de português para libras: (Im)Possibilidades no contexto jurídico - Dias, Lucas Gonçalves (2023)
Few studies have focused on court interpretation involving languages of different modalities, such as Portuguese and Libras (Brazilian Sign Language). However, given the growing demand for Libras translators and interpreters in the legal context, studies are needed to determine the actual role of these professionals and the limitations and implications of their performance in court. Considering that a court interpreter’s performance is strongly correlated with the rights of those needing interpreting assistance, this MA thesis aims to understand the impact of the interpreter's interpretive choices on the principles of isonomy and due process of law. To this end, an investigation was developed in two stages. In the first stage, a theoretical-practical study was carried out based on a review of the relevant literature (within Legal Science, Translation and Interpretation Studies, Lexical Science, and Expertise Studies) and on the author’s practice in court interpretation. In a second stage, a quasi-experiment was performed (i.e., with real lifelike tasks performed in a controlled situation) whereby two interpreters – one with training and experience in court interpretation (P2); and another without this experience (P1) – were asked to perform two Portuguese-Libras interpreting tasks containing as stimuli audio versions of source texts characteristic of judicial proceedings (complaint submission, and custody hearing). Considering the different proportions of legal lexemes or phrasemes in these texts, the interpreting strategies/tactics and the interpreting errors of these two professionals were analyzed in order to discuss whether their linguistic choices correlate with the fulfillment of a court interpreter’s legal duty and whether specialized training in court interpretation seems to be indicative of any impact on professional performance. The first stage findings showed to the limitations of a court interpreter’s performance, as they should avoid strategies/tactics and errors that imply “deviations” to the source text as much as possible within their cognitive constraints. The second stage findings showed that the participant with specialized training performed better in interpreting the complaint submission stimulus, which contained denser text with a greater concentration of lexemes and phrasemes that are not part of the general language. The results point to the highly specialized nature of the court interpreter's work, which, as a public service interpreting job, requires consistent specialized training, and a greater understanding of all parties involved about their expert status in the Brazilian legal context.